Community-based tourism: concepts, opportunities and challenges - Aditha Agung Prakoso; Eugenius Pradipto; Muhammad Sani Roychansyah; Bima Setya Nugraha (Goodwood Publishing, 2020)
Purpose: The community-based tourism concept needs to be understood deeply. We need to know and predict the opportunities and challenges that exist and will occur in the future in developing the community and tourism as a mutualism. This research analyzed the theories to describe it and derive conclusions for the basic concepts of community-based tourism as well as further explore the cases of applying these concepts to gain opportunities and challenges from community-based tourism Research methodology: This study is a conceptual article using the literature review method Results: This study elaborates the concepts, opportunities and challenges of the community-based tourism paradigm. Limitations: This study is a secondary data-based analysis (literature review) on the concept of community-based tourism in the social and cultural context of the community, as well as the opportunities and challenges of its application to tourism development Contribution: This study provides an in-depth and comprehensive view of community-based tourism to assist in exploring approaches and theories in community-based tourism research and planning and policymaking in the tourism sector, especially in the local community aspect.